Effects on freezing - thawing cycles on mechanical properties of PVA hydrogel - How, Lavinia Ai Chen (Nanyang Technological University, 2024)
Hydrogels are crosslinked polymer network with great absorbance ability, able to trap water volumes within their network. In this work, the focus will be on polyvinyl alcohol (PVA) hydrogel, which is a widely used hydrogel, that has found its way into many fields such as drug delivery, bioengineering and tissue engineering. In recent years, PVA hydrogel with high mechanical strength has been researched as a way of replacing organs. This paper aims to investigate the mechanical strength of PVA hydrogel that were synthesized through repeated freezing and thawing (F-T) cycles. The tensile strength is tested using a universal mechanical tester, then Young’s modulus is calculated. Research findings suggest that the Young’s modulus increases with increasing number of F-T cycles.